27. ATTITUDES AND FACTORS RELATED TO THE PROFESSION OF NURSING STUDENTS OF HANOI MEDICAL COLLEGE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the attitude towards the nursing profession and some related factors of nursing students of Hanoi Medical College in 2024.Subject and method: The cross-sectional study was conducted on 218 full-time college nursing students from the first to the third year of Hanoi Medical College from April to October 2024.Results: The percentage of Nursing students with a positive attitude towards the profession is 89.9%. The T-test test shows that the gender factors, reasons for choosing the nursing profession with relatives who are medical staff, personal interests, family advice, training programs, facilities of the University, and plans to study to a higher level are related to the attitude of nursing students towards the profession.Conclusion: Nursing students have a high percentage of positive attitudes towards the profession. Factors related to attitudes towards the nursing profession include: 1. Gender; 2. Reasons for choosing the nursing profession with relatives who are medical staff; 3. Choose a profession according to personal interests; 4. Choose a profession according to the advice of the family; 5. Training programs; 6. The school's facilities; 7. Planning to study to a higher level.
Keywords: Attitude; the nursing profession; nursing students